Handbook of petrochemical processes - Speight, James G. (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
"The petrochemical industry is a scientific and engineering field that encompasses the production of a wide range of chemicals and polymers. The purpose of this book is not only to provide a follow-on to form the later chapters of the highly successful Chemistry and Technology of Petroleum 5th Edition but also provides a simplified approach to a very diverse chemical subject dealing with the chemistry and technology of various petroleum and petrochemical process. Following from the introductory chapters, this book provides the readers with a valuable source of information containing insights into petrochemical reactions and products, process technology, and polymer synthesis. Provides readers with a valuable source of information containing insights into petrochemical reactions and products, process technology, and polymer synthesis Introduces the reader to the various petrochemical intermediates are generally produced by chemical conversion of primary petrochemicals to form more complicated derivative products The reactions and processes involved in transforming petroleum-based hydrocarbons into the chemicals that form the basis of the multi-billion dollar petrochemical industry are reviewed and described The book includes information on new process developments for the production of raw materials and intermediates for petrochemicals Includes a description of the origin of the raw materials for the petrochemicals industry - including an overview of the coal chemicals industry"--
4.3.2 Cracking Processes4.3.2.1 Thermal Cracking Processes; 4.3.2.2 Catalytic Cracking Processes; 4.3.3 Dehydrogenation Processes; 4.3.4 Dehydrocyclization Processes; 4.4 Streams from Coal, Oil Shale, and Biomass; 4.4.1 Coal; 4.4.1.1 Coal Gas; 4.4.1.2 Coal Liquids; 4.4.2 Oil Shale; 4.4.2.1 Oil Shale Gas; 4.4.2.2 Shale Oil; 4.4.3 Biomass; 4.4.3.1 Biogas; 4.4.3.2 Bio-liquids; References; Chapter 5 Feedstock Preparation by Gasification; 5.1 Introduction; 5.2 Gasification Chemistry; 5.2.1 General Aspects; 5.2.2 Pretreatment; 5.2.3 Reactions; 5.2.3.1 Primary Gasification
OCLC-licensed vendor bibliographic record.
Keywords: Petroleum -- Refining; Petroleum chemicals; Chemical processes; TECHNOLOGY & ENGINEERING / Power Resources / General; SCIENCE / Chemistry / General; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY / Engineering / Chemical & Biochemical